1999
DOI: 10.1046/j.1365-8711.1999.02750.x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectra of the RIXOS source sample

Abstract: A B S T R A C TWe present results of an extensive study of the X-ray spectral properties of sources detected in the RIXOS survey, which is a large, nearly complete sample of objects detected serendipitously in ROSAT PSPC fields down to a flux limit of 3 Â 10 214 erg cm 22 s 21 (0.5± 2 keV). We show that for X-ray surveys containing sources with low count rate, such as RIXOS, spectral slopes estimated using simple hardness ratios in the ROSAT band can be biased. Instead, we analyse three-colour X-ray data using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 42 publications
6
36
0
Order By: Relevance
“…However the amount of observational results that cannot be explained in terms of the unified model of AGN is also significant. There is a substantial number of type-1 AGN for which X-ray absorption has been detected (Mittaz et al 1999;Fiore et al 2001;Page et al 2001;Schartel et al 2001;Tozzi et al 2001b;Mainieri et al 2002;Brusa et al 2003;Page et al 2003;Carrera et al 2004;Perola et al 2004;Mateos et al 2005), as well as Seyfert 2 galaxies unabsorbed in X-rays (Pappa et al 2001;Panessa et al 2002;Barcons et al 2003;Mateos et al 2005). The origin of the X-ray absorption in type-1 AGN is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…However the amount of observational results that cannot be explained in terms of the unified model of AGN is also significant. There is a substantial number of type-1 AGN for which X-ray absorption has been detected (Mittaz et al 1999;Fiore et al 2001;Page et al 2001;Schartel et al 2001;Tozzi et al 2001b;Mainieri et al 2002;Brusa et al 2003;Page et al 2003;Carrera et al 2004;Perola et al 2004;Mateos et al 2005), as well as Seyfert 2 galaxies unabsorbed in X-rays (Pappa et al 2001;Panessa et al 2002;Barcons et al 2003;Mateos et al 2005). The origin of the X-ray absorption in type-1 AGN is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…There are not enough counts in the jet-like feature to do a detailed spectral analysis. However, the hardness ratios in Table 2 of the sources detected therein indicate a somewhat harder spectrum than the power law spectrum with photon index of 1.7 of NGC 6217 (see Mittaz et al 1999 and HR1 1.0, HR2 ∼ 0.2 compared to 0.89 and 0.00). While the feature is clearly extended from NGC 6217 to the SW it cannot be resolved by the PSPC in the perpendicular direction.…”
Section: Observations and Resultsmentioning
confidence: 94%
“…Mittaz et al (1999) characterized the X-ray spectra of the extragalactic objects in the RIXOS survey based on power law fits on three broad-band X-ray colors assuming galactic absorption. This method only gives reasonable fits if the intrinsic spectrum really can be described by a power law.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…The average dust color temperature in the region was determined to be 27±4 K. We also determined the dust temperature distribution throughout the nebular region by dividing the 100 mm map by the 60 mm map and comparing the resulting I(100mm)/ I(60mm) values at each map location with the values given for dust grain models by Mittaz (1999). We found that the dust color temperature of the southern nucleus is 34±4 K and the temperature of its northern counterpart 32±4 K. The eastern filamentary structures are slightly cooler (20±2 K) than the western filamentary structures (26±3 K).…”
Section: Temperature Distance and Mass Estimatementioning
confidence: 99%